Introducing Mutations to Modify the C13/C9 Ratio in Linoleic Acid Oxygenations Catalyzed by Rabbit 15‐Lipoxygenase: A QM/MM and MD Study1. Issue 18 (3rd September 2014) - Suardíaz, Reynier; Masgrau, Laura; Lluch, José M.; González‐Lafont, Àngels
Abstract Lipoxygenases (LOs) are a family of nonheme iron‐containing enzymes that catalyze the hydroperoxidation of several polyunsaturated fatty acids with a huge regio‐ and stereospecificity. Mammalian 15‐LO‐1 yields almost exclusively oxygenation at the C13 position of the linoleic acid (LA), its preferred substrate. This is very important because metabolites derived from oxidation in distinct positions produce opposite physiological effects. We have combined here quantum mechanics/molecular mechanics calculations with molecular dynamics simulations to show how a suitable mutation of the rabbit 15‐LO‐1 enzyme can produce a significant amount of products derived from oxygenation at the C9 position of LA. In effect, the Leu597Val or Leu597Ala mutants are predicted to lead to a diminution of the oxygenation C13/C9 ratio in LA as huge as five orders of magnitude. This shows that the conserved residue Leu597 actually drives the regiospecific hydroperoxidation of LA catalyzed by 15‐LO‐1 enzyme.